1997
DOI: 10.1074/jbc.272.6.3674
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the 90K Immunostimulator Gene Is Controlled by a Promoter with Unique Features

Abstract: 90K is a secreted glycoprotein with tumor suppressive functions, which is up-regulated in various types of cancer and in AIDS. In order to understand the regulation of its expression, the mouse 90K gene was isolated and analyzed. The gene spans about 8.8-kilobase pairs and consists of 6 exons and was localized on chromosome 11, region E. RNase protection identified one major transcription start site (؉1) and three minor ones (؊3, ؉32, ؉34). The mouse 90K gene was found to have a TATAless promoter of unusual st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Additionally, the mouse CyCAP gene reported here has an intron-exon structure and promoter sequence identical to the mouse 90K gene, which was isolated by virtue of hybridization to hMac-2-BP cDNA (ref. 38 and data not shown). These data establish CyCAP as the sequence most similar to hMac-2-BP in the mouse genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the mouse CyCAP gene reported here has an intron-exon structure and promoter sequence identical to the mouse 90K gene, which was isolated by virtue of hybridization to hMac-2-BP cDNA (ref. 38 and data not shown). These data establish CyCAP as the sequence most similar to hMac-2-BP in the mouse genome.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have proposed that hMac-2-BP may be involved in host defense to pathogens (8,12,16,38). Biochemical studies showing an interaction between hMac-2-BP and LPS and its receptor CD14 (17) suggested that the role of hMac-2-BP in defense may be through the host response to endotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…A few promoters have been described that, like the DD3 promoter, are TATA-less and initiator-less and are not GC-rich (Ref. 29, and references therein). No further similarities to these gene promoters could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…2). This region has been reported to be the minimal promoter of the mouse and human 90K genes (35,36) and, as will be evident below, corresponds to the minimal functional promoter of the rat 90K as well.…”
Section: Characterization Of the 5ј-flanking Region Of The Rat 90k Genementioning
confidence: 99%
“…Sequence alignments and comparisons with the human and mouse 5Ј-flanking regions (35,36) were performed using Gene Works (IntelliGenetics, Inc., Mountain View, CA).…”
Section: Dna Sequencing and Sequence Analysismentioning
confidence: 99%